Feasibility Study of VUV Sensitization Effect of Tb3+ - Mikhailik, V; Kraus, H (2010)
The possibility to use Tb3+ as luminescence sensitizer for enhancement of the conversion efficiency of vacuum-ultraviolet (VUV) radiation into visible light was examined. We studied the luminescence properties of K3Tb(PO4)2 and Ba3Tb(PO4)3 activated by Eu3+, and of SrAl12O19 co-doped with Mn2+ and Tb3+ at excitation over the 120 to 300nm wave-length range. It is shown that Tb3+ ions, exhibiting a strong absorption band in the VUV, can provide efficient sensitization of Eu3+ and Mn2+ emissions for excitation in this spectral range, giving rise to intense red and green luminescence, respectively. This study provides a proof for the concept of VUV sensitization, which enables the engineering of luminescence materials with improved efficiency for excitation from a noble gas discharge. © Taylor and Francis Group, LLC.